PELATIHAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA GURU - Renni Ramadhani Lubis; Mustafa Habib; Muhammad Sadri; Nurhamimah Rambe; Wina Mariana; Titin Rahmayanti Rambe; Yusda Novianti; Haryati Haryati (JMM (Jurnal Masyarakat Mandiri), 2022)
Abstrak: Tujuan dari pelatihan ini yaitu untuk meningkatkan kompetensi guru dalam menggunakan model pembelajaran berbasis proyek untuk meningkatkan hasil belajar siswa SD IT Hamas. Kegiatan ini dilaksanakan dalam bentuk pelatihan model pembelajaran berbasis proyek bagi guru. Peserta kegiatan pelatihan ini berjumlah 20 orang yang merupakan guru dari SD IT Hamas. Berdasarkan hasil yang telah diperoleh, bahwa kegiatan pengabdian kepada masyarakat ini telah terlaksana dengan baik sesuai dengan harapan tim pengabdian dan peserta. Persentase capaian pelaksanaan kegiatan pengabdian masyarakat selama 2 hari adalah 97,35%.Abstract: The purpose of this training is to improve the competence of teachers in using project-based learning models to improve student learning outcomes of SD IT Hamas. This activity is carried out in the form of project based learning model training for teachers. The participants of this training activity were 20 people who were teachers from the Hamas IT Elementary School. Based on the results that have been obtained, that this community service activity has been carried out well in accordance with the expectations of the service team and participants. The percentage of achievements in the implementation of community service activities for 2 days is 97.35%.